2008
DOI: 10.1121/1.2839900
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of vocal-tract influence during saxophone performance

Abstract: This paper presents experimental results that quantify the range of influence of vocal tract manipulations used in saxophone performance. The experiments utilized a measurement system that provides a relative comparison of the upstream windway and downstream air column impedances under normal playing conditions, allowing researchers and players to investigate the effect of vocal-tract manipulations in real time. Playing experiments explored vocal-tract influence over the full range of the saxophone, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
48
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 21 publications
(27 reference statements)
6
48
0
1
Order By: Relevance
“…Musicians shape their mouth to stabilize and influence frequency and timbre of the note (Hoekje, 1986;Fritz and Wolfe, 2005;Guillemain, 2007, Scavone et al, 2008, Chen et al 2009). The vocal tract (mouth cavity) can be included in the simulation program, this is not done here.…”
Section: Theory Of Time Domain Simulationsmentioning
confidence: 99%
“…Musicians shape their mouth to stabilize and influence frequency and timbre of the note (Hoekje, 1986;Fritz and Wolfe, 2005;Guillemain, 2007, Scavone et al, 2008, Chen et al 2009). The vocal tract (mouth cavity) can be included in the simulation program, this is not done here.…”
Section: Theory Of Time Domain Simulationsmentioning
confidence: 99%
“…The range of frequencies over which the vocal tract is used for pitch bending in the second register of the clarinet ͑well within the normal range of the instrument͒ is comparable with the range for which Scavone et al ͑2008͒ reported vocal tract effects for the alto saxophone ͑520-1500 Hz͒. This range is also comparable with that reported for vocal tract tuning in a study on tenor saxophones: To play in the very high ͑altissimo͒ range, saxophonists tune their vocal tract resonance ͑Chen et al, 2008͒, but they do not do so in the normal range.…”
Section: Vocal Tract Resonance In Normal Playing and Pitch Bendingmentioning
confidence: 99%
“…This was particularly observed in saxophones and clarinets during altissimo playing and for special effects such as pitch bending. [4][5][6][7][8]15,16 Regarding lip-reed instruments, experiments on the didjeridu 17 showed anti-resonances in the radiated sound induced by vocal-tract resonances. Wolfe et al investigated the influence of upstream resonances in the didgeridoo and trombone performance using an artificial lip reed player.…”
Section: Introductionmentioning
confidence: 99%